Pengaruh kualitas layanan perpustakaan terhadap tingkat kepuasan pengguna di perpustakaan UIN Sayyid Ali Rahmatullah Tulungagung - Della Hanifa Putri Suryani; Nurul Setyawati Handayani (UIN Mataram, 2023)
The quality of service at the UIN Sayyid Ali Rahmatullah Tulungagung library is measured based on the results of a descriptive analysis of Tangible, Responsiveness (response), Assurance (guarantee), Empathy (empathy) given by librarians in serving users is good and a total score of 3733 is obtained or 70.43% means that the quality of service at the UIN Sayyid Ali Rahmatullah Tulungagung library is good. User satisfaction at the UIN Sayyid Ali Rahmatullah Tulungagung library is measured by the theory of Libqual Service of Affect. Users feel satisfied when receive services from librarians, library as place user feel satisfied when they are in the library, information control users feel satisfied when they receive instructions and access facilities provided. by librarians, a total score of 520 or 65.40% of users felt satisfaction when they received services from the UIN Sayyid Ali Rahmatullah Tulungagung library. The effect of service quality on user satisfaction in the UIN Sayyid Ali Rahmatullah Tulungagung library has a strong and positive significant value, the data is obtained from a simple linear regression test, if the service quality is higher then the user's perceived satisfaction is also high, supported by the dimension of service quality that give satisfaction to users such as concrete evidence of the availability and completeness of the collection, the infrastructure owned by the library such as tables, chairs, shelves, reading rooms, neatness of the staff. Reliability, thoroughness, expertise, discipline of office in serving user needs, discipline and timeline of office in serving users. Good and fast response of officers to complaints and user needs. Guaranteed timely certainty in service and also guaranteed certainty of meeting the needs of users. Officer empathy prioritizes serving user needs, officers are friendly and polite in serving user needs, do not discriminate between services to users Officers respect user needs.